(untitled) (Dhaka University Journal of Biological Sciences, 2023)
Soil fertility is one of the most promising factors that directly impact sustainable crop production. Therefore, a pot experiment was conducted in net house on capsicum (Capsicum annuum L.) in the agricultural soil to study the effects of vermicompost (VC) and inorganic fertilizers (NPK) on growth, yield and nutrient content in capsicum plants. The growth parameters and nutritional values were observed during the experiment under eleven treatments. The treatments variables are T1 (control, -VC & -NPK), T2 (VC 5 ton/ha), T3 (VC 10 ton/ha), T4 (VC 15 ton/ha), T5 (N60P35K60 kg/ha), T6 (VC 5 ton/ha +N48P28K48 kg/ha), T7 (VC 10 ton/ha + N48P28K48 kg/ha), T8 (VC 15 ton/ha + N48P28K48 kg/ha), T9 (VC 5 ton/ha + N36P21K36 kg/ ha), T10 (VC 10 ton/ha + N36P21K36 kg/ha), T11 (VC 15 ton/ha + N36P21K36 kg/ha) which were arranged in a completely randomized design (CRD) with three replications. There were statistically significant differences in each treatment for growth and yield parameters. The highest plant height (45 cm), the highest number of leaves (44 no/plant), and the highest leaf area index (90 cm2) were found in the treatments T6, T5 and T9 respectively. The lowest values for all of the above parameters were found in the treatment T1 (control). Then the highest yield parameters fruit no/ plant (3), total fresh weight (39.60 g/plant), and total dry weight (2.38 g/plant) were observed under the treatment T11. The results of the growth and yield parameters varied significantly (p<0.05). The concentrations of total N, P, K and S in different parts were measured and varied significantly (p<0.05) in leaf, stem, root and seeds. Analysis of post-harvest soil also revealed that every physico-chemical property and nutritional value were changed significantly due to different treatments. Dhaka Univ. J. Biol. Sci. 32(1): 73-81, 2023 (January)